Revision of Total Knee Arthroplasties Performed in Young, Active Patients with Posttraumatic Arthritis and Osteoarthritis - Old, Andrew Brian; Long, William John; Scott, W. Norman (The Journal of Knee Surgery, 2017)
Rates of total knee arthroplasty (TKA) in younger patients are rising significantly. A recent study performed at our institute illustrated the excellent survivorship of TKAs in patients younger than 55 years at a mean follow-up period of 25 years. This study reports on the 25 knees in this series that required revision surgery. Twenty-five revisions were performed in 24 patients. Indication for revision, clinical outcomes, and radiographs were reviewed at their most recent follow-up. Revisions were performed in 5 cases of infection, 2 cases of fracture/trauma, 17 cases of wear/loosening, and 1 case of instability. The average duration from primary TKA to revision surgery for the 25 knees was 12.5 years (range, 2–26 years). Follow-up was obtained in 24 of 25 TKAs. Nine of the 24 patients (10 knees) had died at the time of follow-up. The average duration from revision surgery to follow-up examination for the remaining knees was 10.5 years. Using the Knee Society scoring system, the average knee score was 89.0 points and the average functional score was 75.6 points. The mean Tegner activity score was 4.6 which exceeded the mean score for unrevised TKAs (2.9). The average range of motion was 119 degrees. None of the knee radiographs showed evidence of component loosening. Young patients who undergo TKA that require revision surgery had good mid-term clinical outcomes. This information is important in completing the clinical picture and outcomes associated with young patients undergoing TKA.
Keywords: young patient; revision of total knee arthroplasty; osteoarthritis; outcomes